Pemanfaatan Media Tiga Dimensi Pop Up Book dalam Meningkatkan Hasil Belajar IPA Materi Ekosistem pada Siswa Kelas V SDN 03 Clering Donorojo Jepara - Cahyono, Gatot Pujo; Widiyono, Aan (Indo-MathEdu Intellectuals Journal, 2023)
This research is based on the atmosphere of the learning process that is alive and effective, less active students and low learning motivation and learning outcomes of students in grade V SDN 03 Clering. This study aims to determine how effective the application of Pop-Up Book media is in improving science learning outcomes of ecosystem material in grade V elementary school students "N 03 Clering Donorojo Jepara.  "This research is an experimental quantitative study with pre-Experimental research types and One-Group Pretest-Posttest Design." The study was conducted in grade V SDN 03 Donorojo Jepara with a total of 30 respondents. The results of the "paired samel t-test analysis showed that the calculated value obtained was greater than the ttable (8,746 > 2,042) the application of Pop-Up Book media was effective in learning outcomes of science student ecosystem material in grade V SDN 03 Donorojo for the 2023/2024 school year.